PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI THA-IT SUKSA SCHOOL NONTHABURU BANGKOK THAILAND - Zubdatul Awwaliyah; Chalimatus Sa’dijah; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The principal in an educational role is very important in achieving the desired educational goals, must really master the management of the organization, what strategies will be used to advance the institutions owned, must be able to become top leaders who are ready to compete with other schools, because the principal must Being a role model in a school institution, the principal must have an attitude that is trustworthy, responsible, has strong and wise principles that make the principal a person who can be respected and respected and also a role model in doing all activities. The success of the principal can also be seen from how the strategies used in leading and building commitments, combining the right vision and mission, and also managing resources that support and achieve goals. in developing the quality of school education, the quality of education in Thailand Tha-It Suksa Nonthaburi School is increasingly becoming a favorite school in Nonthaburi, this is evidenced by the existence of various religious programs and customs that refer to the Qur'an and the Hadith of the Prophet, implementing programs to improve and develop students who will take part in competitions, and prepare students for the National Examination.